Area Of A Triangle

Geometry Level 4

In the diagram above A B = 2 B C AB = 2BC , A B D D B C = 6 0 \angle{ABD} \cong \angle{DBC} = 60^{\circ} and B D = 100 BD = 100 .

If the area of A B C \triangle ABC can be expressed as A A B C = a b a c A_{\triangle{ABC}} = a b^a \sqrt{c} , where a a , b b , and c c are coprime positive integers, find a + b + c a + b + c .


The answer is 80.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Nibedan Mukherjee
Jan 18, 2020

Rocco Dalto
Jan 18, 2020

Using the Law of sines for A B D \triangle{ABD} we have:

2 3 A D = 2 y sin ( 18 0 m ) = 2 y sin ( m ) \dfrac{2}{\sqrt{3}}AD = \dfrac{2y}{\sin(180^{\circ} - m)} = \dfrac{2y}{\sin(m)} \implies A D = 3 y sin ( m ) AD = \dfrac{\sqrt{3}y}{\sin(m)}

and using the Law of sines for D B C \triangle{DBC} we have:

2 3 D C = y sin ( m ) D C = 3 y 2 sin ( m ) \dfrac{2}{\sqrt{3}}DC = \dfrac{y}{\sin(m)} \implies DC = \dfrac{\sqrt{3}y}{2\sin(m)}

A D D C = 2 \implies \dfrac{AD}{DC} = 2 .

Let D C = x A D = 2 x DC = x \implies AD = 2x .

Using the law of cosines for A B D \triangle{ABD} we have:

4 x 2 = 4 y 2 + 10 0 2 400 y cos ( 6 0 = 4 y 2 200 y + 10 0 2 4x^2 = 4y^2 + 100^2 - 400y\cos(60^{\circ} = 4y^2 - 200y + 100^2

x 2 = y 2 50 y + 2 5 2 4 \implies x^2 = y^2 - 50y + 25^2 * 4

and using the law of cosines for D B C \triangle{DBC} we have:

x 2 = y 2 + 10 0 2 200 y cos ( 6 0 ) = y 2 100 y + 2 5 2 4 2 x^2 = y^2 + 100^2 - 200y\cos(60^{\circ}) = y^2 - 100y + 25^2 * 4^2

y 2 50 y + 2 5 2 4 = y 2 100 y + 2 5 2 4 2 50 y 4 2 5 2 3 = 0 \implies y^2 - 50y + 25^2 * 4 = y^2 - 100y + 25^2 * 4^2 \implies 50y - 4 * 25^2 * 3 = 0 \implies

y = ( 2 ) ( 50 ) ( 25 ) ( 3 ) 50 = 150 y = \dfrac{(2)(50)(25)(3)}{50} = 150

x 2 = 15 0 2 50 ( 150 ) + 2 5 2 4 = 2 5 2 6 2 2 5 2 12 + 2 5 2 4 = 2 5 2 ( 28 ) = \implies x^2 = 150^2 - 50(150) + 25^2 * 4 = 25^2 * 6^2 - 25^2 * 12 + 25^2 * 4 = 25^2(28) =

2 5 2 2 2 7 x = 50 7 A C = 3 x = 150 7 25^2 * 2^2 * 7 \implies x = 50\sqrt{7} \implies AC = 3x = 150\sqrt{7}

and A D = 2 x = 100 7 = 3 y sin ( m ) = 150 3 sin ( m ) AD = 2x = 100\sqrt{7} = \dfrac{\sqrt{3}y}{\sin(m)} = \dfrac{150\sqrt{3}}{\sin(m)} \implies

sin ( m ) = 3 2 3 7 \sin(m) = \dfrac{3}{2}\sqrt{\dfrac{3}{7}} and A D = 100 AD = 100 \implies height h h of A B C \triangle{ABC} is h = 100 ( 3 2 ) 3 7 h = 100(\dfrac{3}{2})\sqrt{\dfrac{3}{7}}

= 150 3 7 = 150\sqrt{\dfrac{3}{7}}

A A B C = 1 2 ( 150 7 ) ( 150 3 7 ) = \implies A_{\triangle{ABC}} = \dfrac{1}{2}(150\sqrt{7})(150\sqrt{\dfrac{3}{7}}) = 2 2 5 2 3 2 3 = 2 * 25^2 * 3^2\sqrt{3} =

2 ( 75 ) 2 3 = a b a c a + b + c = 80 2 (75)^2\sqrt{3} = a * b^a * \sqrt{c} \implies a + b + c = \boxed{80} .

Chew-Seong Cheong
Jan 19, 2020

Let B C = x BC = x ; then A B = 2 x AB = 2x . Let B A C = θ \angle BAC = \theta . By sine rule ,

{ A B B D = sin A D B sin B A D 2 x 100 = sin ( 12 0 θ ) sin θ . . . ( 1 ) B C B D = sin B D C sin B C D x 100 = sin ( 6 0 + θ ) sin ( 6 0 θ ) . . . ( 2 ) \begin{cases} \dfrac {AB}{BD} = \dfrac {\sin \angle ADB}{\sin \angle BAD} & \implies \dfrac {2x}{100} = \dfrac {\sin (120^\circ - \theta)}{\sin \theta} & ...(1) \\ \dfrac {BC}{BD} = \dfrac {\sin \angle BDC}{\sin \angle BCD} & \implies \dfrac x{100} = \dfrac {\sin (60^\circ + \theta)}{\sin (60^\circ -\theta)} & ...(2) \end{cases}

( 1 ) ( 2 ) : 2 = sin ( 12 0 θ ) sin θ × sin ( 6 0 θ ) sin ( 6 0 + θ ) Note that sin ( 18 0 ϕ ) = sin ϕ = sin ( 6 0 + θ ) sin θ × sin ( 6 0 θ ) sin ( 6 0 + θ ) = sin ( 6 0 θ ) sin θ = 3 2 cot θ 1 2 \begin{aligned} \frac {(1)}{(2)}: \quad 2 & = \frac {\blue{\sin(120^\circ - \theta)}}{\sin \theta} \times \frac {\sin(60^\circ - \theta)}{\sin (60^\circ+\theta)} & \small \blue{\text{Note that }\sin (180^\circ - \phi) = \sin \phi} \\ & = \frac {\blue{\sin(60^\circ + \theta)}}{\sin \theta} \times \frac {\sin(60^\circ - \theta)}{\sin (60^\circ+\theta)} \\ & = \frac {\sin(60^\circ - \theta)}{\sin \theta} \\ & = \frac {\sqrt 3}2 \cot \theta - \frac 12 \end{aligned}

tan θ = 3 5 sin θ = 21 14 , cos θ = 5 7 14 \implies \tan \theta = \dfrac {\sqrt 3}5 \implies \sin \theta = \dfrac {\sqrt{21}}{14}, \cos \theta = \dfrac {5\sqrt 7}{14} and from ( 1 ) (1) :

2 x 100 = sin ( 6 0 + θ ) sin θ = 3 2 × 5 7 14 + 1 2 × 21 14 21 14 = 3 x = 150 A A B C = 1 2 A B × B D sin 6 0 + 1 2 B C × B D sin 6 0 = 1 2 ( 300 + 150 ) ( 100 ) ( 3 2 ) = 2 ( 7 5 2 ) 3 \begin{aligned} \frac {2x}{100} & = \frac {\sin (60^\circ + \theta)}{\sin \theta} = \frac {\frac {\sqrt 3}2 \times \frac {5\sqrt 7}{14} + \frac 12 \times \frac {\sqrt{21}}{14}}{\frac {\sqrt {21}}{14}} = 3 \\ \implies x & = 150 \\ A_{\triangle ABC} & = \frac 12 AB \times BD \sin 60^\circ + \frac 12 BC \times BD \sin 60^\circ \\ & = \frac 12 (300+150) (100) \left(\frac {\sqrt 3}2\right) \\ & = 2(75^2)\sqrt 3 \end{aligned}

Therefore a + b + c = 2 + 75 + 3 = 80 a+b+c = 2+75+3 = \boxed {80} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...